2003
DOI: 10.1103/physrevb.67.052101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defect-induced internal field on the aging of relaxors

Abstract: The effect of a defect-induced internal field on the dielectric response of relaxor ferroelectrics is investigated using a Monte Carlo simulation. It was observed that only at a small temperature range near the temperature of the dielectric maximum does the susceptibility decrease markedly due to the internal field. This temperature range increases with enhancing internal field. We found that the susceptibility is almost independent of the internal field width at low internal field width, and then decreases li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In practice, the composite may have various types of "defects" (such as particle aggregations) and the performances of the two phases may be very different from their "standard" properties (e.g., the piezoelectric behavior of PZT may show a nonlinear dependence on the electrical field and time), which may result in deviation of the experimental data from simulation results. 27,28 Theoretical and experimental investigations on the influences of structural "defects" on the ME coefficients are in progress.…”
Section: -mentioning
confidence: 99%
“…In practice, the composite may have various types of "defects" (such as particle aggregations) and the performances of the two phases may be very different from their "standard" properties (e.g., the piezoelectric behavior of PZT may show a nonlinear dependence on the electrical field and time), which may result in deviation of the experimental data from simulation results. 27,28 Theoretical and experimental investigations on the influences of structural "defects" on the ME coefficients are in progress.…”
Section: -mentioning
confidence: 99%
“…12,56,81 In order to overcome the CD etch loading effects and reduce write time on the e-beam write tool, negative-tone resist has obtained intense study recently. 82 In order to obtain a good I/D bias results in final layer, I/D bias on resist layer should be controlled in a low level before plasma etch. Because of higher load than regular clear field photomasks with positive-tone photoresist ͑e.g., 30%-50%͒, etch time will be significantly longer if the same etch recipe was used as regular clear field masks, resulting in a low selectivity which may result in a radial CD distribution instead of the loading-related CD distribution.…”
Section: Numbermentioning
confidence: 99%
“…[13][14][15] It is observed that the dielectric aging follows linear logarithmic time dependence and the aging can be characterized by a thermally activated process. 16 There have been numerous different models and mechanisms invoked to elucidate the origin of aging. 16 There have been numerous different models and mechanisms invoked to elucidate the origin of aging.…”
Section: Introductionmentioning
confidence: 99%